2018
DOI: 10.1002/anie.201809754
|View full text |Cite
|
Sign up to set email alerts
|

Diphosphahexaarenes as Highly Fluorescent and Stable Materials

Abstract: Oligoarenes are regarded as subunits of p-extended carbon nanoforms,s uch as graphene and nanotubes,w ith exceptional technological importance.F used arenes can thus providef undamental insight into the nature of the electronic properties of fused polyaromatic rings and pave the way for the design of extended graphene-like materials.However,large pextended arenes often show lowstability.Herein we report the straightforwardp reparation of linearly fused diphosphahexaarenes containing two six-membered phosphorus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 45 publications
4
44
0
1
Order By: Relevance
“…As a result, large laterally fused aromatic systems are rather challenging to characterize, especially by spectroscopic techniques. With this in mind, we envisaged the synthesis of novel diphosphahexaarenes, formed by six linearly fused six‐membered rings bearing two phosphorus centers (Figure ) . It is worth noting that, strictly speaking, the diphosphahexaarenes cannot be considered as acenes since they possess two off‐line rings.…”
Section: Phosphorus Heteroarenes: the Originmentioning
confidence: 99%
See 4 more Smart Citations
“…As a result, large laterally fused aromatic systems are rather challenging to characterize, especially by spectroscopic techniques. With this in mind, we envisaged the synthesis of novel diphosphahexaarenes, formed by six linearly fused six‐membered rings bearing two phosphorus centers (Figure ) . It is worth noting that, strictly speaking, the diphosphahexaarenes cannot be considered as acenes since they possess two off‐line rings.…”
Section: Phosphorus Heteroarenes: the Originmentioning
confidence: 99%
“…In addition, all derivatives were soluble in a series of organic solvents including ethanol, acetonitrile, chloroform, dichloromethane, and tetrahydrofuran. X‐ray diffraction studies revealed an essentially planar scaffold for all diphosphahexaarenes, although 52a exhibited a slightly curved structure . In the solid state, the diphosphahexaarenes formed dimeric structures by π‐stacking with different degrees of overlap.…”
Section: Phosphorus Heteroarenes: the Originmentioning
confidence: 99%
See 3 more Smart Citations